What Europe? Fortress, different speeds, coloniser or archipelago - Tomaz Ponce Dentinho (European Regional Science Association (ERSA), 1998)
The paper starts with the introduction of a simple analytical tool that classifies regions according to their scale and accessibility. Those indicators are closely related to the strategies of European expansion and European integration and at the same time translate paradigmatic outcomes of those combined strategies; they are usually labelled as fortress Europe, different speeds Europe, coloniser Europe and, adding one more, an archipelago of European Regions. The paper then uses European regional statistics in order to access the structure and evolution of the Europe that has being built.
Keywords: 330